Student's guide for Chemistry : the central science Brown, LeMay, Bursten, tenth edition - Hill, James C. 4 0 16; (Theodore Lawrence), 1928- Brown, Theodore L.; 5 (Upper Saddle River, NJ : Pearson Prentice Hall, 2006)
Chemistry: The Central Science is the most trusted book on the market--its scientific accuracy, clarity, innovative pedagogy, functional problem-solving and visuals set this book apart. Brown, LeMay, and Bursten teach students the concepts and skills they need without overcomplicating the subject. A comprehensive media package that works in tandem with the text helps students practice and learn while providing instructors the tools they need to succeed.--Publisher's description.
Matter and measurement -- Atoms, molecules and ions -- Stoichiometry: calculations with chemical formulas and equations -- Aqueous reactions and solution stoichiometry -- Thermochemistry -- Electronic structure of atoms -- Periodic properties of the elements -- Basic concepts of chemical bonding -- Molecular geometry and bonding theories -- Gases -- Intermolecular forces, liquids, and solids -- Modern materials -- Properties of solutions -- Chemical kinetics -- Chemical equilibrium -- Acid-base equilibria -- Additional aspects of aqueous equilibria -- Chemistry of the environment -- Chemical thermodynamics -- Electrochemistry -- Nuclear chemistry -- Chemistry of the nonmetals -- Metals and metallurgy -- Chemistry of coordination compounds -- The chemistry of life: organic and biological chemistry.
Includes index.
Includes index.
For grades 12.
Keywords: 2 -- 0; 6; Chemistry;Chemistry -- 20 -- Study guides.;Problems, exercises, etc; 20; 2